Cooperative dynamic non-zero-sum of two-person game - Vakrinienė, S. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: С. Вакринене. Кооперативная динамическая неантагонистическая игра двух лиц S. Vakrinienė. Kooperatinis dinaminis neantagonistinis dviejų asmenų lošimas